ANALISIS PENERAPAN PENDEKATAN SAINTIFIK DALAM KURIKULUM 2013 DI KELAS V SD NEGERI 13 PEKANBARU - Muharmiati, Meri; Hermita, Neni; Guslinda, Guslinda (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2020)
This study aims to describe the application of the scientific approach in the curriculum 2013 in class VB Public Elementary School 13 of Pekanbaru. This research is a descriptive qualitative study. The subjects in this study were teachers of class VB Public Elementary School 13 of Pekanbaru. Data collection techniques used in this study include: observation, interviews and documentation. The results of the study show that the teacher has carried out learning activities by applying the scientific approach. Activities carried out in learning include observing activities, the questioning activity, the activity of trying, reasoning, dan communicating activities. To activities of teacher of class VB SDN 13 Pekanbaru has carried out learning by applying the scientific approach but has not been implemented optimally.